2006
DOI: 10.1136/bjo.2005.082503
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blindness and cataract surgery in Gandaki Zone, Nepal

Abstract: Background/aim: Himalaya Eye Hospital (HEH), established in 1993, is rendering eye care services in the Gandaki and Dhaulagiri zones. The hospital has extensive community outreach activities along with services for outpatients, emergencies, and subspecialties such as vitreoretinal, paediatric, and low vision. The operation theatre is well equipped to match the surgical needs including phaco surgery for cataract. The hospital has performed more than 14 000 cataract surgeries and 250 000 treatment services durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
74
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 7 publications
(22 reference statements)
11
74
4
2
Order By: Relevance
“…Female preponderance was also seen in Gandaki Zone. 6 Similar results were obtained in Lumbini Zone and Chetwan district of Nepal where women constituted 52% and 53% of the total enumerated and examined population, respectively. 7 This is different from most hospital based studies where there is a male preponderance.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Female preponderance was also seen in Gandaki Zone. 6 Similar results were obtained in Lumbini Zone and Chetwan district of Nepal where women constituted 52% and 53% of the total enumerated and examined population, respectively. 7 This is different from most hospital based studies where there is a male preponderance.…”
Section: Discussionsupporting
confidence: 72%
“…In a study performed in Gandaki Zone, 6 cataract was the principal cause of blindness in 60.5%. Other causes of visual impairment were refractive error (11.7%), macular degeneration (8.7%), and corneal opacities (8%).…”
Section: Discussionmentioning
confidence: 99%
“…18,[20][21][22] Even though our finding is in accordance with a previous report from Nepal; OR: 1.30, (95% CI: 0.90, 1.80), however, further studies are warranted to confirm this finding. 23 There exists an association between presence of diabetes and CS both in bivariable and multivariable analysis. Persons with presence of diabetes had significantly lower odds of prevalence of CS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the zonal surveys carried out by Sapkota et al (2006) in Gandaki Zone, cataract was found to be the principal cause of blindness (60.5%) and refractive error was the dominant cause (83.3%) of vision impairment (<6/19). Similarly, in population-based prevalence surveys on blindness and visual impairment done in nine countries by Limburg H et al (2008), cataract was found to be the main cause of blindness (41 -87%) followed by posterior segment diseases (7 -47%).…”
Section: Resultsmentioning
confidence: 99%